Silent ischemia: Silent after all? - D’Antono, Bianca (Pulsus Group Inc, 2008)
OBJECTIVE: To examine the association of nonpain symptoms in men and women with exercise-related silent ischemia, as well as the independence of these findings from other clinical factors. METHODS: A prospective study of 482 women and 425 men (mean age 58 years) undergoing exercise stress testing with myocardial perfusion imaging. Analyses were performed on 60 women and 155 men with no angina but medical perfusion imaging evidence of ischemia during exercise. MEASURES: The presence of various non-pain-related symptoms. Ischemia is indicated by myocardial perfusion defects on exercise stress testing with single photon emission computed tomography. RESULTS: Women reported more nonangina symptoms than men (P<0.05). They experienced fatigue, hot flushes, tense muscles, shortness of breath and headaches more frequently (P<0.05). Symptoms relating to muscle tension and diaphoresis were associated with ischemia after controlling for pertinent clinical covariates. However, the direction of association differed according to sex and history of coronary artery disease events or procedures. Sensitivity of the detection models showed modest improvements with the addition of these symptoms. CONCLUSIONS: While patients who experience silent ischemia experience a number of nonpain symptoms, those symptoms may not be sufficiently specific to ischemia, nor sensitive in detecting ischemia, to be of particular help to physicians in the absence of other clinical information.